Activation–retardation in sol–gel reactions for additive manufacturing of transparent poly(methylsilsesquioxane) aerogels - Gao, Mengyue; Zhang, Junyan; Xu, Chengjian; Yu, Xiaoxiao; Chen, Linfeng; Zheng, Junjie; Zuo, Weiwei; Zhang, Xinhai; Cheng, Yanhua; Zhu, Meifang (Nature communications, 2025)
Coupling superior thermal insulation performance with high transparency for solar transmission and excellent processability in aerogels is a challenging yet promising subject. Here, we report a direct ink writing strategy to create transparent polymethylsilsesquioxane (PMSQ) aerogels from gel inks with desired rheology, by merely using acid-base dual modulators to achieve “activation–retardation” of polycondensation reaction. The printed aerogels are pure PMSQ, have a transmittance of 97% in the visible-near infrared range, thermal conductivity (16.2 mW m −1 K −1 ) lower than that of still air, and low density (0.08 g cm −3 ). We demonstrate new possibilities of our 3D-printed transparent aerogels, such as device encapsulation for heat insulation and cylindrical cooling shields for lighting. Authors report a direct ink writing strategy to create transparent polymethylsilsesquioxane aerogels from gel inks with desired rheology, using acid-base dual modulators to achieve “activation–retardation” of polycondensation reaction.